Application of HEC-RAS 1D and 2D Flood Risk Modelling along the Old Brahmaputra River, Jamalpur - Rakib, Muhammad Rezaul (The Jahangirnagar Review, 2024)
Bangladesh is extremely susceptible to floods and experienced with massive damages to lives and properties over the years. The current strategy for flood control of the Old Brahmaputra floodplain region lacks implication of explicit knowledge of flood mapping which can reduce the flood-induced loss regarding lives and economy. This study generates a flood inundation model to find out the spatial extent of flood risk areas along the Old Brahmaputra floodplain in Jamalpur. Available SRTM-DEM of 2014, river discharge and water level data (1988 and 2020) of Jamalpur and Mymensingh station are used in this HEC-RAS 1D and 2D flood modelling. From the model results, it is revealed that extent of flood inundation varies according to the water level and also 1D and 2D simulation method where 1D results are more suitable to the observed water level rather than 2D results. All the unions of Jamalpur Sadar are not inundated by floods equally where Tulsir Char union is having with highest inundation experience. Besides, 1988 flood caused the maximum inundation then 2020 flood event. Moreover, DEM resolution, cross sections, mess size and Manning’s coefficient (n) stimulus the model results. Along with structural flood mitigation strategies, this modelling approach is a strategic technique for better preparedness, community awareness, and strategy formulation to flood.